2018
DOI: 10.1021/acs.orglett.8b03619
|View full text |Cite
|
Sign up to set email alerts
|

Regioselective Transition-Metal-Free Oxidative Cyclobutanol Ring Expansion to 4-Tetralones

Abstract: A facile and transition-metal-free ring expansion of the cyclobutanol moiety to 4-tetralones fused to heteroaromatic systems is described. The oxidative ring expansion proceeds rapidly and regioselectively through mediation by N-bromosuccinimide and acetonitrile in satisfactory to good yields. The preparation of precursors and the ring expansion have proven to be scalable and are straightforward to carry out.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(37 citation statements)
references
References 25 publications
1
36
0
Order By: Relevance
“…The groups of Zhang and Kim, on the other hand, were particularly productive in the area of tandem functionalization/semi‐pinacol rearrangements and pioneered the electrochemical synthesis of a variety of β‐functionalized cyclopentanones from vinyl‐substituted cyclobutanols [17–20,22] . Although protocols for the ring expansion of cyclobutanols to tetralones under traditional synthetic methods (e. g. [Ag], [29] [Rh], [30] [Pd], [31,32] [Ce], [33] N ‐bromosuccinimide [34–36] ) were previously disclosed, a two‐carbon ring homologation to tetralones under mild and ecological electrochemical techniques has not yet been accomplished (Scheme 1).…”
Section: Methodsmentioning
confidence: 99%
“…The groups of Zhang and Kim, on the other hand, were particularly productive in the area of tandem functionalization/semi‐pinacol rearrangements and pioneered the electrochemical synthesis of a variety of β‐functionalized cyclopentanones from vinyl‐substituted cyclobutanols [17–20,22] . Although protocols for the ring expansion of cyclobutanols to tetralones under traditional synthetic methods (e. g. [Ag], [29] [Rh], [30] [Pd], [31,32] [Ce], [33] N ‐bromosuccinimide [34–36] ) were previously disclosed, a two‐carbon ring homologation to tetralones under mild and ecological electrochemical techniques has not yet been accomplished (Scheme 1).…”
Section: Methodsmentioning
confidence: 99%
“…60 The use of four-membered ring building blocks in medicinal chemistry remains relatively underdeveloped as chemists depend on a small number of viable protocols towards these moieties. 61,62 Given our laboratory's interest in the use of fourmembered rings to access biologically relevant scaffolds, [63][64][65][66][67][68] we questioned if we could expand the scope of C2-alkenylation protocols to hitherto virtually inaccessible 2-(cyclobut-1-en-1yl)-1H-indole analogues through a transition-metal-free cyclobutenylation/deprotection cascade (Scheme 1c). Our implementation of these design criteria and computational studies on the mechanistic details are described herein.…”
Section: Introductionmentioning
confidence: 99%
“…We had demonstrated that treatment of heteroaromatic-substituted cyclobutanols with N-bromosuccinimide (NBS) in acetonitrile yielded the desired 4-tetralones (Scheme 3). 17 We would now like to describe advances in the scope and limitations of our methodology to convert cyclobutanols to 4tetralones, as well as supply additional information on the mechanism of this transformation.…”
Section: ■ Introductionmentioning
confidence: 99%